2020
DOI: 10.5713/ajas.19.0031
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of dry-aging and wet-aging on physicochemical properties and digestibility of Hanwoo beef

Abstract: Objective: The purpose of this study was to investigate the effects of aging methods (AM) i.e. dry-aging (DA) and wet-aging (WA) on the physicochemical properties and in vitro digestibility of proteins in beef short loin.Methods: Short loins (M. longissmus lumborum), were trimmed and boned-out on the fifth day postmortem, from a total of 18 Hanwoo, which were purchased from a commercial slaughterhouse. Short loins were separated randomly grouped into one of the three treatments: control, WA (1°C, 7 days), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 20 publications
0
7
0
2
Order By: Relevance
“…WHC showed an increasing trend as the aging period increased at all temperatures. In meat, WHC has a positive correlation with pH [ 34 ], and this study also showed that the pH and WHC of the meat dry aged using the electric field refrigeration system have a positive correlation. As the pH increases, the number of anion increased and it spread the gap between muscle fibers, which increases the space that can store water, resulting in a higher WHC [ 35 ].…”
Section: Resultsmentioning
confidence: 60%
“…WHC showed an increasing trend as the aging period increased at all temperatures. In meat, WHC has a positive correlation with pH [ 34 ], and this study also showed that the pH and WHC of the meat dry aged using the electric field refrigeration system have a positive correlation. As the pH increases, the number of anion increased and it spread the gap between muscle fibers, which increases the space that can store water, resulting in a higher WHC [ 35 ].…”
Section: Resultsmentioning
confidence: 60%
“…Therefore, the total collagen content was not significantly affected by the dry-aging process. The content of soluble proteins and soluble collagen in meat could be influenced by other factors related to species and animal (within the same species or the same animal: age, sex, race, fattening status); factors related to the type of muscle considered, type II (rapid contraction/glycolytic metabolism) and type I (slow contraction/oxidative metabolism) ( 125 ).…”
Section: Biochemical Characteristics and Changes During Meat Dryingmentioning
confidence: 99%
“…Fuente: Elaboración propia La determinación de las PC permite inferir la posibilidad de experiencia de consumo dada su alta correlación con la jugosidad de la carne (Warner, 2017), por lo cual podríamos deducir que los resultados de maduración a los 21 días, obtenidos en el presente estudio, pueden estar relacionados con mayor jugosidad, tal como se observó en el análisis sensorial (figura 1). Por otro lado, las diferencias reportadas en las pérdidas por cocción se pueden asociar al efecto del proceso de maduración en la carne y sus cambios en la estructura muscular (Kim et al, 2020;Macharáčková et al, 2020;Yun et al, 2020), tales como disminución en el tamaño de la fibra muscular, aumento en el espacio entre miofibras y menor diámetro del sarcómero (Purslow et al, 2016). Como resultado, la literatura reporta que la pieza de carne incrementa el intercambio o pérdida de agua celular propiciado por la desnaturalización térmica de las proteínas (Astruc et al, 2010;Bouhrara et al, 2011;Christensen et al, 2011;Li et al, 2010).…”
Section: Tabla 2 Rendimientos Cárnicos En Machos Blanco Orejinegrounclassified
“…Agropecuaria,22(3) Respecto a la maduración, contrario a lo descrito en la literatura, en la cual se indica que la proteólisis causada por la maduración conduce a mayor pérdida de agua en la carne en la cocción (Purslow et al, 2016), en la presente investigación se evidenció que las muestras de LT de BON maduradas a 37 días, presentaron menores pérdidas por cocción, comparadas con las muestras de menos días de maduración. Otros autores también han reportado menores perdidas por cocción en procesos de maduración húmedos y secos a 30 días (Kim et al, 2020), o a diferentes edades (5 y 21 días) y con varios músculos (longissimus thoracis y longissimus lumborum) (Macharáčková et al, 2020;Yun et al, 2020).…”
Section: Tabla 2 Rendimientos Cárnicos En Machos Blanco Orejinegrounclassified